SURVEY OF THE ROLE OF GUIDANCE AND COUNSELING TEACHER IN DISTRIBUTING THE TALENT AND INTEREST OF STUDENTS AT NORTH JAKARTA VOCATIONAL HIGH SCHOOL - Heru Sriyono (International Journal of Research Science and Management, 2017)
This study aims to find out about the Role of Guidance and Counseling Teacher in Distributing the Talent and Interest of Students at North Jakarta Vocational High School. The research method used in this research is qualitative method with descriptive approach, that is how to collect real data, what is at the time of research conducted. Sources of data in this study are students of class XI Accounting, amounting to 40 students and class XI Office Administration amounting to 20 students as a sample of research or data sources totaling 60 students. Determination of data source using purposive sampling technique. The research instruments used in this research are observation, interview and questionnaire. Observations were made by observing the school environment and the state of the school, interviewing the principal and teacher guidance and counseling and questionnaire addressed to students or respondents. Data analysis technique is done by collecting data, grouping data, analyzing data, and interpreting data and then concluded as research result. The conclusion of the research result is the Role of Guidance and Counseling Teacher in Distributing Talent and Student Interest in Vocational High School Nusantara North Jakarta in good enough category.